Pertanggungjawaban Pidana Korporasi Multinasional Dalam Pencucian Uang Lintas Negara: Kekosongan Hukum Internasional - Fika Labuda Aziz; Asep Suherman (GLOBAL SCIENTS PUBLISHER, 2026)
Multinational corporations are increasingly identified as key actors in complex transnational money laundering networks, yet the existing international legal regime has not been able to effectively address the criminal liability of corporate entities. This article examines the gap in international law in the context of multinational corporations' criminal liability for transnational money laundering crimes, using a normative juridical approach through a literature review of international legal instruments, corporate criminal law doctrine, and relevant theoretical perspectives. The analysis shows that international legal instruments such as the United Nations Convention against Transnational Organized Crime (UNTOC 2000), the United Nations Convention against Corruption (UNCAC 2003), and the Financial Action Task Force (FATF) recommendations are still not directly criminally binding on corporations and rely on implementation through each country's national legislation. This legal gap creates jurisdictional loopholes that are systematically exploited by multinational corporations through multi-layered, cross-jurisdictional corporate structures. This article recommends the establishment of an international legal instrument that explicitly recognizes the subjectivity of corporate criminal law at the international level and establishes a direct and binding enforcement mechanism.